(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
We experienced that there are various internet of things (IoT) solutions rising in recent years which created applications in many companies and many developing countries. Authors mainly use qualitative analysis regarding to internet of things issues and applications and design for emerging markets including Vietnam. Therefore, this papers aims to analyzes it and proposes some recommendations for IoT design solutions in emerging markets and Vietnam. For instance, authors summarized and analyzed solutions such as: applications for smart house and solutions for office building with IoTs uses such as warning system and cameras, as well as initial principles to set up IoT design.